Grammar and Punctuation - Ricky Telg; Ashley McLeod-Morin (EDIS)
This 4-page publication covering proper grammar and punctuation for news media writing is the third of a five-part series on news media writing. This series also covers an introduction to news media writing, news writing for print, news writing for television and radio, and interviews for news stories. Minor revision by Ricky Telg and Ashley McLeod-Morin; published by the UF/IFAS Department of Agricultural Education and Communication.